Competency-Based Human Resource Development Strategy in Islamic Boarding Schools - Alwi Taufik; Agus Setiawan; Mispani Mispani (CV. Bimbingan Belajar Assyfa, 2025)
This study aims to analyze competency-based human resource (HR) development strategies in Islamic boarding schools (pesantren). As the oldest Islamic educational institutions in Indonesia, pesantren face significant challenges in developing the competencies of educators and administrators amidst demands for modernization, globalization, and digital transformation. Many pesantren, particularly salafiyah pesantren, have not yet implemented systematic and sustainable HR development systems, resulting in teacher and educational staff competencies that do not meet expected standards. This research employs a qualitative approach with a case study method in several pesantren in Lampung Province. Data were collected through in-depth interviews with pesantren leaders (kyai), administrators, and educators, participatory observation, and documentation of HR development programs. The findings reveal that competency-based HR development strategies in pesantren are implemented through four main pillars: (1) HR planning involving needs analysis and competency mapping; (2) recruitment and selection of educators based on pedagogical, personality, social, and professional competency criteria; (3) competency development through internal training, internships, advanced studies, and collaboration with external parties; and (4) continuous performance evaluation and career development. Supporting factors include visionary kyai leadership, strong pesantren organizational culture, and administrator commitment, while inhibiting factors include limited funding, facilities, information access, and resistance to change. This study concludes that planned, systematic, and sustainable competency-based HR development strategies are key to improving the quality of education in pesantren without neglecting Islamic values and local wisdom.